A MANAGEMENT APPROACH TO COMPONENT OBSOLESCENCE IN THE MILITARY ELECTRONIC SUPPORT ENVIRONMENT - Meyer, A.; Pretorius, L.; Pretorius, J.H.C. (The South African Journal of Industrial Engineering, 2012)
ENGLISH ABSTRACT: This article proposes a process to manage the problem of electronic component obsolescence from a military product support perspective. By assessing applicable literature as well as feedback and lessons learned from relevant support projects, a methodology for the management of component obsolescence is proposed. The aim of the research is to provide a definition of component obsolescence drivers and to formulate a process for the management of component obsolescence within a military electronic support environment. The process provides guidelines on how management activities can be optimised to reduce applicable obsolescence risks and thereby reducing related life cycle costs. AFRIKAANSE OPSOMMING: Hierdie artikel stel